Growing Up at the "Margins": Concerns, Aspirations, and Expectations of Young People Living in Nairobi's Slums. (14th February 2013) - Kabiru, Caroline W.; Mojola, Sanyu A.; Beguy, Donatien; Okigbo, Chinelo
<x xml:space="preserve">Abstract</x> We explore the concerns, challenges, aspirations, and expectations of sub‐Saharan African youth, and investigate how these youth cope with neighborhood constraints to aspiration achievement. We draw on cross‐sectional survey data from 4033 12–22‐year‐olds (50.3% males) from two Kenyan urban slums and subsequent in‐depth interviews conducted with a subset of 75 youth when they were 13–24 years old (45.3% males). We observe that despite the challenges characteristic of urban slums, some youth maintain high aspirations and try to achieve them through education, delinquency, residential mobility, and religion. We note that others adjust their aspirations to account for limited opportunities. Overall, our findings highlight positive youth agency and underscore the need to improve the quality of life in urban slums.